Effects of Food Authenticity, Food Quality, Place Dependence, Place Identity, and Service Quality on Tourist Satisfaction during COVID-19 - Puja Anggara, Agung; Adi Sistha Winata, Gede (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
Tourism is vital for Bali, Indonesia's economy, celebrated for its cultural and natural splendor. Yet, the global Covid-19 pandemic posed unprecedented challenges, compelling a reevaluation of factors crucial for tourist satisfaction. The purpose of this research is to determine the effect of food authenticity, food quality, place dependability, place identity, and service quality on traveler satisfaction during Covid-19 in Bali, Indonesia. The research method used in this study is quantitative. With a population of 425 respondents surveyed by questionnaire from tourists who visited Bali and tasted culinary products while traveling to certain destinations in Bali. Data was analyzed by multiple linear regression.  The results of this study show (1) Food authenticity, food quality, place dependability, place identity, and service quality are significantly positively related to tourist satisfaction. (2) Food authenticity, food quality, place dependence, place identity, and service quality have a positive effect on tourist satisfaction. This study concludes that local food (food authenticity and quality), place attachment (place dependence and identity), and service quality are important factors affecting tourist satisfaction. The research implicates that enhancing local food offerings, ensuring authenticity and quality, strengthening place attachment through reliable infrastructure and meaningful identity, and maintaining high service standards are important strategies to improve tourist satisfaction. Amid ongoing global challenges such as the Covid-19 pandemic, focusing on these factors can not only improve the traveler experience but also support tourism recovery and growth in Bali, Indonesia. Future efforts should prioritize these aspects to maintain and enhance Bali's appeal as a tourist destination.